Durable Biopolymer Films From Lignin-Carbohydrate Complex Derived From a Pulp Mill Side Stream - Asikanius, Brita; Jääskeläinen, Anna-Stiina; Koivula, Hanna; Oinonen, Petri; Österberg, Monika (Frontiers in Energy Research, 2021)
Valorization of side streams offers novel types of raw materials to complement or replace synthetic and food-based alternatives in materials science, increasing profitability and decreasing the environmental impacts of biorefineries. Lignocellulose biomass contains lignin and carbohydrates that are covalently linked into lignin-carbohydrate complexes (LCCs). In biomass fractionation processes, these complexes are conventionally considered as waste, which hinders the biomass fractionation process, and they may solubilize into aqueous effluents. This study presents how LCCs, derived from pulp mill effluent, can be turned into valuable biopolymers for industrial polymer film applications. Free-standing composite films containing hydroxyethyl cellulose (HEC) and LCCs with varying molar mass, charge density and lignin/hemicellulose ratio were prepared to study the effect of LCC amount on mechanical properties and oxygen permeability. Increasing the LCC content increased the yield point and Young’s modulus of the films. Breaking strain measurements revealed a non-linear correlation with the LCC concentration for the samples with higher lignin than hemicellulose content. The addition of LCC enhanced oxygen barrier properties of HEC films significantly even at high relative humidity. The present research demonstrates how a currently underutilized fraction of the biorefinery side stream has the potential to be valorized as a biopolymer in industrial applications, for example as a barrier film for paper and board packaging.